Relevance of multiple basin drainage and primary histologic regression in prognosis of trunk melanoma patients with negative sentinel lymph nodes. (23rd September 2012) - Ribero, S; Quaglino, P; Osella‐Abate, S; Sanlorenzo, M; Senetta, R; Macrì, L; Savoia, P; Macripò, G; Sapino, A; Bernengo, M.G
Abstract: Background  Lymphatic drainage to multiple basins (MLBD) is frequently observed in patients with primary melanoma located in the trunk. Conflicting data regarding the prognostic impact of MLBD are reported. Objective and methods  We reviewed our case series of 352 patients with trunk melanoma to evaluate the pattern of basin drainage and to analyse whether different basin drainages may have different significance in negative sentinel lymph node (SLN) patients. The presence of single/multiple basin drainage, the status of SLN, the presence of melanoma regression, Breslow thickness, ulceration and type of melanoma were recorded for each patients and correlated to Disease Free Survival (DFS) and Overall Survival (OS). Results  MLBD occurred in 77 patients (21.9%) and single basin lymphatic drainage (SLBD) occurred in 275 patients (79.1%). The presence of metastases in SLN was not significantly different in patients with MLBD compared to those with SLBD (26% vs. 19.6%). No differences in OS and DFS were found in SLBD/MLBD independently from SLN status. However DFS was higher in patients with MLBD and negative SLN ( P  = 0.0001), in addition, in patients with negative SLN and SLBD disease recurrence was 19% while was only 7% in patients with negative SLN obtained from MLBD ( P  = 0.03). Multivariate analysis showed that Breslow thickness <2 mm, MLBD pattern and regression of melanoma were favourable variables for DFS of patients with negative SLN. Conclusions  An accurate study of the drainage basin and of all the SLNs obtained from MLBD is recommended because of the impact in prognosis of melanoma of the trunk.